2006
DOI: 10.1105/tpc.105.040279
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of theArabidopsisSyntaxin PEP12/SYP21 Inhibits Transport from the Prevacuolar Compartment to the Lytic Vacuole in Vivo

Abstract: Golgi-mediated transport to the lytic vacuole involves passage through the prevacuolar compartment (PVC), but little is known about how vacuolar proteins exit the PVC. We show that this last step is inhibited by overexpression of Arabidopsis thaliana syntaxin PEP12/SYP21, causing an accumulation of soluble and membrane cargo and the plant vacuolar sorting receptor BP80 in the PVC. Anterograde transport proceeds normally from the endoplasmic reticulum to the Golgi and the PVC, although export from the PVC appea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
113
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(119 citation statements)
references
References 67 publications
5
113
1
Order By: Relevance
“…Figure 1B shows that none of the total a-amylase activities (medium + cells) is reduced, thus ruling out cell mortality as a cause for induced secretion. By contrast, an increase in the total activity was seen in samples where vacuolar sorting was inhibited, which is explained by a higher stability of the reporter in the culture medium compared with the vacuole (Foresti et al, 2006).…”
Section: Identification Of Rab Gtpases Involved In Vacuolar Sortingmentioning
confidence: 52%
See 1 more Smart Citation
“…Figure 1B shows that none of the total a-amylase activities (medium + cells) is reduced, thus ruling out cell mortality as a cause for induced secretion. By contrast, an increase in the total activity was seen in samples where vacuolar sorting was inhibited, which is explained by a higher stability of the reporter in the culture medium compared with the vacuole (Foresti et al, 2006).…”
Section: Identification Of Rab Gtpases Involved In Vacuolar Sortingmentioning
confidence: 52%
“…Vam3 is a tail-anchored transmembrane SNARE that has been extensively used as a tonoplast marker (Saito et al, 2002;Uemura et al, 2002) and a green fluorescent protein (GFP)-Vam3 fusion was previously shown not to interfere with vacuolar sorting (Foresti et al, 2006).…”
Section: Vacuolar Delivery Of Gfp-vam3 Is Dependent On the Action Of mentioning
confidence: 99%
“…In these cases, whether active sorting processes are required for these pathways is not clear, since proteins destined to the central lytic vacuole or the PSV are secreted out of the cell when vacuolar trafficking pathways are inhibited by various treatments, including overexpression of VSR/BP80 and RMR mutants or overexpression of the PVC-localized t-SNARE AtPEP12p (Shimada et al, 2003;Sohn et al, 2003;daSilva et al, 2005;Park et al, 2005;Foresti et al, 2006;Fuji et al, 2007;Craddock et al, 2008). The number of different routes for protein secretion and trafficking of plasma membrane proteins in plant cells is unknown.…”
Section: The Anterograde Trafficking Pathways At the Golgi Apparatusmentioning
confidence: 99%
“…However, it is most likely that VAMP727 overexpression increases the incorporating efficiency for other Qa-SNAREs that have functions redundant with SYP22. The SYP21 protein could be a candidate for such a Qa-SNARE because it is also involved in traffic from the PVC (Foresti et al, 2006).…”
Section: Vamp727 Is a Multicopy Suppressor Of Syp22mentioning
confidence: 99%